History Practicum On Syarikat Eastern Smelting Bhd. : A Brief History Of A Smelting Company With Reference To The History Of Malaysian Tin Industry, 1869-1966 - Yunus, Junian Haji (Universiti Sains Malaysia, 1974)
Our research was mainly concentrated at the Company’s office at 75, Dato Keramat Road, Penang. The necessary Secondary Background reading was done at the University’s Library at Minden and also at the company’s Library.